COVID‐19: From pathogenesis models to the first drug trials. Issue 5 (23rd June 2020) - Brüssow, Harald
Summary: The number of people infected with SARS‐CoV‐2, and sadly dying from COVID‐19, has exploded, and so the amount of literature on the novel coronavirus and the disease it causes has increased proportionately. The case numbers in some countries are beyond the epidemic peak, but the uncertainty about a second wave keeps politicians and societies under pressure. Appropriate decision‐making and winning support from the population depends on precise scientific information rather than leaving the field to scaremongers of all proveniences. This mini‐review is an update of earlier reports (Brüssow, Microb Biotechnol 2020a;13:607; Brüssow, Microb Biotechnol 2020b; https://doi.org/10.1111/1751-7915.13592 ).